Destabilization of vitelline membrane outer layer protein 1 homolog (VMO1) by C‐mannosylation. Issue 3 (30th January 2023) - Yoshimoto, Satoshi; Suzuki, Takehiro; Otani, Naoki; Takahashi, Daisuke; Toshima, Kazunobu; Dohmae, Naoshi; Simizu, Siro
Abstract : C ‐mannosylation is a rare type of protein glycosylation whereby a single mannose is added to the first tryptophan in the consensus sequence Trp‐Xaa‐Xaa‐Trp/Cys (in which Xaa represents any amino acid). Its consensus sequence is mainly found in proteins containing a thrombospondin type‐1 repeat (TSR1) domain and in type I cytokine receptors. In these proteins, C ‐mannosylation affects protein secretion, intracellular localization, and protein stability; however, the role of C ‐mannosylation in proteins that are not type I cytokine receptors and/or do not contain a TSR1 domain is less well explored. In this study, we focused on human vitelline membrane outer layer protein 1 homolog (VMO1). VMO1, which possesses two putative C ‐mannosylation sites, is a 21‐kDa secreted protein that does not contain a TSR1 domain and is not a type I cytokine receptor. Mass spectrometry analyses revealed that VMO1 is C ‐mannosylated at Trp 105 but not at Trp 44 . Although C ‐mannosylation does not affect the extracellular secretion of VMO1, it destabilizes the intracellular VMO1. In addition, a structural comparison between VMO1 and C ‐mannosylated VMO1 showed that the modification of the mannose changes the conformation of three loops in VMO1. Taken together, our results demonstrate the first example of C ‐mannosylation for protein destabilization of VMO1. Abstract : Human VMO1 possesses two putative C‐mannosylation sites. Mass spectrometry analyses showed that VMO1 is C ‐mannosylated at Trp 105 but not at Trp 44 . When a single mannose is attached to Trp 105 of VMO1, Maestro predicted that the structural conformation of VMO1 changes. In addition, C ‐mannosylation destabilized VMO1. This study is the first example of C ‐mannosylation leading to protein destabilization.